Automated Content Based Image Retrieval Using Wavelets. - Irfan, A.; Sumari, P. (2004)
Automated image retrieval from large databases using content-based image retrieval (CBIR) is in great demand nowadays as many areas such as medical and journalism rely on CBIR systems to perform their job.